Vertical wind profile in the abnospheric surface boundary layer in winter at Phuoc Hoa (Binh Dinh) - Lưu, Lê Văn; Huy, Lê Việt; Thành, Phạm Xuân; Sơn, Hoàng Hải (Vietnam Journal of Earth Sciences, 2018)
Based on wind data measured at Phuoc Hoa (Binh Dinh)...